Surgery of Moyamoya Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The manifestations of moyamoya disease in children and adults and the results of various surgical procedures are reviewed from the Department of Neurological Surgery and Section of Child and Adolescent Neurology, Mayo Clinic, Rochester, MN.